Is quality important to our patients? The relationship between surgical outcomes and patient satisfaction. Issue 1 (3rd November 2017) - Lobo Prabhu, Kristel; Cleghorn, Michelle C; Elnahas, Ahmad; Tse, Alvina; Maeda, Azusa; Quereshy, Fayez A; Okrainec, Allan; Jackson, Timothy D
Abstract : Background: With greater transparency in health system reporting and increased reliance on patient-centred outcomes, patient satisfaction has become a priority in delivering quality care. We sought to explore the relationship between patient satisfaction and short-term outcomes in patients undergoing general surgical procedures. Methods: Satisfaction surveys were distributed to patients following discharge from the general surgery service at an academic hospital between June 2012 and March 2015. Short-term clinical outcomes were obtained from the American College of Surgeons National Surgical Quality Improvement Program database. Patients rated their level of satisfaction on a 5-point Likert scale, and ordered logistic regression model was used to determine predictors of high patient satisfaction. Results: 757 patient satisfaction surveys were completed. The mean age of patients surveyed was 52.2 years; 60.0% of patients were female. The majority of patients underwent a laparoscopic procedure (85.9%) and were admitted as inpatients following surgery (72%). 91.5% of patients rated satisfaction of 4–5, and 95.0% said they would recommend the service. The odds of overall satisfaction were lower in patients who had complications (OR: 0.52, 95% CI 0.31 to 0.87) and 30-day readmission (OR: 0.35, 95% CI 0.17 to 0.70). Having elective surgery was associated with higher odds of satisfaction (OR: 1.62, 95% CI 1.07 to 2.47). Conclusions: We found a significant association between patient satisfaction and both 30-day readmission and the occurrence of postoperative surgical complications. Given this association, further study is warranted to evaluate patient satisfaction as a healthcare quality indicator.